Iron Chelators in Treatment of Iron Overload - Sarina Entezari; Seyedeh Mona Haghi; Narges Norouzkhani; Barsa Sahebnazar; Fatemeh Vosoughian; Diba Akbarzadeh; Muhammad Islampanah; Navid Naghsh; Mohammad Abbasalizadeh; Niloofar Deravi (Journal of Toxicology)
Patients suffering from iron overload can experience serious complications. In such patients, various organs, such as endocrine glands and liver, can be damaged. Although iron is a crucial element for life, iron overload can be potentially toxic for human cells due to its role in generating free radicals. In the past few decades, there has been a major improvement in the survival of patients who suffer from iron overload due to the application of iron chelation therapy in clinical practice. In clinical use, deferoxamine, deferiprone, and deferasirox are the three United States Food and Drug Administration-approved iron chelators. Each of these iron chelators is well known for the treatment of iron overload in various clinical conditions. Based on several up-to-date studies, this study explained iron overload and its clinical symptoms, introduced each of the above-mentioned iron chelators, and evaluated their advantages and disadvantages with an emphasis on combination therapy, which in recent studies seems a promising approach. In numerous clinical conditions, due to the lack of accurate indicators, choosing a standard approach for iron chelation therapy can be difficult; therefore, further studies on the issue are still required. This study aimed to introduce each of these iron chelators, combination therapy, usage doses, specific clinical applications, and their advantages, toxicity, and side effects.